Regulatory decisions in the context of risk and uncertainty - Szkudlarek, Piotr (Decyzje regulacyjne w kontekście ryzyka i niepewności, 2020)
The purpose of the article is to identify the propensity of decision-makers of the regulatory authority on the telecommunications market in Poland (Office of Electronic Communications, OEC) in making decisions under risk and uncertainty conditions and comparing them with a group of non-experts. The research outcomes reveal that decision-makers of the regulatory authority make in most cases decisions that are consistent with the prospect theory. In addition, OEC decision-makers in circumstances of uncertainty, retain the status quo and maintain a lower risk tendency in a decision-making situation with the same expected value but different variance. It was pointed out, at the same time, that their decisions did not differ from those taken by the group of non-experts. The findings presented in the article contribute to the discussion on the propensity of public decision-makers to make decisions under conditions of risk and uncertainty
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 107-117